Correlation Between Family Support and Emotional Regulation with The Resilience of Breast Cancer Patients in The City of Surabaya: A Literature Review - Mauna Qurrotul Ain; Mira Triharini; Tiyas Kusumaningrum (Pediomaternal Nursing Journal, 2020)
Introduction: Breast cancer incidence has increased recently. Breast cancer patients usually feel inconvenience, psychological impact, and unstable emotions. The purpose of this study is to review the literature on the relationship between family support and emotional regulation with the resilience of breast cancer patients.Methods: The review literature search uses a database "Google Scholar, Sinta, Jurnal Ners dan Scopus with keywords "Family Support, Emotion Regulation, Resilience, Breast Cancer, Patient" in the last ten years 2009-2019.Results: 4,434 journals then identified for titles obtained as much as 2,142 and filtered according to abstract obtained 98 remaining journals, then review the complete full-text publication of a fully detailed 46 journal The final article that was in accordance with the inclusion criteria was 19 journals (articles).There is a significant relationship between family support and emotional regulation to the resilience of breast cancer patients.Conclusion: Family support can affect the health conditions felt by breast cancer patients; good emotional regulation is needed so that the patient can survive. On the articles that have been reviewed, Family support and hope given to people suffering from chronic diseases can be mediators of the emergence of resilient characters With good emotional regulation Individuals can control emotions by monitoring, evaluating and modifying emotional reactions, thus acquired adaptive emotions and organized behavior, then forming good self-acceptance and the individual feeling confident in him, able to live a life of positive, optimistic, and confident